2020
DOI: 10.1111/gbi.12400
|View full text |Cite
|
Sign up to set email alerts
|

Spherulitic microbialites from modern hypersaline lakes, Rottnest Island, Western Australia

Abstract: Microbialites are organosedimentary deposits formed by the interaction of benthic microbial communities with their environment (Burne & Moore, 1987) and provide the only continuous macroscopic record for life spanning its appearance in the Archean through to the present day (Riding, 2000). Biological, physical, and chemical processes combine to produce an internal structure characteristic of microbialites, which include laminated fabrics and clotted to unlayered fabrics (Kennard & James, 1986).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
2
18
0
1
Order By: Relevance
“…In addition, the resultant [Ca]/[Alk] ratios shift between 5.2 and 76.8, while salinity contents can vary between 16.8 and 373 g/L. Carbonate products documented in these natural settings include micrite muds, peloids, microbialite/skeletal sands, thrombolite mounds and microbial mat‐related spherulites (Figure 9G) to spherulitic microbialites (Figure 9I; Arp et al, 2012; Bischoff et al, 2020; Burne & Moore, 1987; Burne et al, 2014; Moore, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the resultant [Ca]/[Alk] ratios shift between 5.2 and 76.8, while salinity contents can vary between 16.8 and 373 g/L. Carbonate products documented in these natural settings include micrite muds, peloids, microbialite/skeletal sands, thrombolite mounds and microbial mat‐related spherulites (Figure 9G) to spherulitic microbialites (Figure 9I; Arp et al, 2012; Bischoff et al, 2020; Burne & Moore, 1987; Burne et al, 2014; Moore, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Sediments constituted by authigenic polycrystalline spherulites are remarkably rare in Recent saline lacustrine environments, where mud‐size single crystals are volumetrically much more common. Some lacustrine evaporitic settings such as the Great Salt Lake, Kiritimati and Rottnest lagoons represent exquisite exceptions recording exotic Recent calcite spherulite sediments clearly occurring in association with microbial mat‐related structures or their exopolymers in highly saline settings (Arp et al, 2012; Bischoff et al, 2020; Chafetz et al, 2018; Chidsey et al, 2015; Kirkham & Tucker, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the lakes on the mainland of WA, Rottnest Island (30 km off the coast of Perth) hosts permanent hypersaline lakes once connected to the ocean and now closed to any marine influence (Bryan et al ., 2016). These wetlands host highly diverse aquatic microbial communities (Saccò et al ., 2021 a ) and lithifying and non‐lithifying microbial mats (Mendes Monteiro et al ., 2020) including conical spherulitic microbialites (Bischoff et al ., 2020), and a recorded presence of a novel halovirus (called SH1; Porter et al ., 2005). Large populations of trans‐equatorial wading species have been recorded making use of the hypersaline habitats over the last century (Saunders & De Rebeira, 2009), and positive trends in population growth have been found recently, highlighting the importance and conservation value of these unique systems (Mather, 2020).…”
Section: The (Concentrated) Salt Of the Earthmentioning
confidence: 99%
“…Here, groundwater lenses-generated by the high permeability of the widespread Tamala Limestone-are recharged via rainfall and discharge into some of the hypersaline lakes [29]. Recent molecular and biogeochemical investigations have indicated that the permanent hypersaline lakes at Rottnest Island host heterogeneous and delicate microbial communities including lithifying and non-lithifying microbial mats [30], together with spherulitic microbialites [31].…”
Section: Introductionmentioning
confidence: 99%